STUDENTS’ SELF-ESTEEM IN LEARNING ENGLISH AND THEIR HAPPINESS - Alan Hubert Frederick Sanger; Fanny H, Rantung; Mei Restiman Bisara; Juwinner Dedy Kasingku (Nusantara Hasana Journal, 2022)
This study is conducted to find out the level of students' self-esteem in learning English, and the level of students' happiness, and the main purpose is to find out if there is a significant correlation between students' self-esteem in learning English and their happiness. This study is quantitative and descriptive correlative. Two kinds of adapted questionnaires are used according to the nature of this study, and they are Rosenberg Self-Esteem Scale (1965) and The Children's Happiness Scale (Morgan, 2014). The participants of the study are the 141 students at selected private senior high school grade X in Airmadidi, who enroll in the first semester of the 2016/2017 academic school year. The findings show that the level of students' self-esteem in learning English and their level of happiness are high. Moreover, there is a significant correlation between students' self-esteem in learning English and their happiness. It is recommended that English teachers need to maintain the way they teach the students by creating friendly circumstances so the students can feel free to express their feelings in positive ways and the students may learn enjoyably.